Magnetic connectivity and solar energetic proton event intensity profiles at deka-MeV energy - Paassilta Miikka; Vainio Rami; Papaioannou Athanasios; Raukunen Osku; Barcewicz Suvi; Anastasiadis Anastasios (ELSEVIER SCI LTD, 2025)
We present an analysis of the time-intensity profiles of 25 solar energetic proton events at 18.2 MeV, modelled by fitting an analytical function form (a modified Weibull function) to the observed intensities. Additionally relying on previous work that characterized the magnetic connectivity between the event-related solar flare and the observer in these events with three angular parameters, we investigate the fit function parameters, the connectivity parameters, and the iron-to-carbon ratio of the events for dependencies and correlations. We find that the fit parameter controlling the basic shape of the profile (parameter a) is not clearly dependent on the connectivity parameters or the Fe/C ratio, suggesting that the profile shapes of neither well and weakly connected nor generally "impulsive" and "gradual" events differ systematically during the early stages of the event at 1 AU. In contrast, the time scaling of the fit function (parameter b) is at least moderately correlated with both the magnetic connectivity parameters and the Fe/C ratio, in that well-connected and iron-rich events are typically shorter in relative duration than weakly connected and nominal-abundance events; intensity rise times display a similar correlation with the connectivity parameters. We interpret the former result as following from the combined effect of various transport processes acting on the particles in interplanetary space, while the latter is essentially consistent with established knowledge regarding the observed dependence of the time-intensity profile shapes of solar energetic particle events on their magnetic connectivity and heavy ion abundances. The desirability of modelling the particle transport effects in detail and extending the analysis to cover higher energies is indicated. (c) 2022 COSPAR. Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).